The Implementation’s Concept Of Multicultural Education In Islamic Education - Junaidi Arsyad; Maisaroh Ritonga (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
There are many different cultures, ethnicities, languages, skin tones, ethnicities, customs, religions, and beliefs in Indonesia. Because of differences of opinion between tribes, cultures, religions, and other groups, plurality in the field can also lead to conflict, which can harm the community if it is not properly managed with tolerance for one another. The purpose of this study is to ascertain how the multicultural education concept is implemented. This study employs a content analysis-based qualitative approach similar to that of library research. Multicultural education is a method of teaching that takes into account students' diverse backgrounds, religions, and cultures to help them realize their full potential. As a process of developing all potentials that respect plurality and heterogeneity, in order to create mutual respect, understanding, and the formation of characters that are mutually open to differences, the implementation of multicultural education is anticipated to be a solution to diverse cultural realities. The concept of multicultural education based on the Qur'an, such as the concept of knowing and respecting various cultures, races, and religions, as the word of Allah swt. is in line with the implementation of multicultural education in Islamic education. in Q.S. Al Hujurat: 12-13, Ar-Rum: 22, Al-Baqarah: 256 and Asy-Syura: 40. The implementation of multicultural education can be incorporated into the learning process of Islamic Religious Education by including material on humanity (mutual respect, respect for individual differences, and other topics) in all learning including planning, executing and evaluation.